2022
DOI: 10.3390/cancers14112722
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Prebiotic Fiber Provide Gut Microbiota-Driven Benefit in a Survivor to Germ-Free Mouse Translational Model of Breast Cancer

Abstract: The gut microbiota plays a role in shaping overall host health and response to several cancer treatments. Factors, such as diet, exercise, and chemotherapy, can alter the gut microbiota. In the present study, the Alberta Cancer Exercise (ACE) program was investigated as a strategy to favorably modify the gut microbiota of breast cancer survivors who had received chemotherapy. Subsequently, the ability of post-exercise gut microbiota, alone or with prebiotic fiber supplementation, to influence breast cancer out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 108 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…Two groups of pre‐exercise participants and post‐exercise participants were compared. It was observed that the post‐exercise group which was treated with oligofructose showed the lowest tumour volume and the highest amount of rehabilitation 28 . This study can be helpful to obese patients 28 .…”
Section: Prebiotics and Their Health Benefitsmentioning
confidence: 76%
See 2 more Smart Citations
“…Two groups of pre‐exercise participants and post‐exercise participants were compared. It was observed that the post‐exercise group which was treated with oligofructose showed the lowest tumour volume and the highest amount of rehabilitation 28 . This study can be helpful to obese patients 28 .…”
Section: Prebiotics and Their Health Benefitsmentioning
confidence: 76%
“…It was observed that the post‐exercise group which was treated with oligofructose showed the lowest tumour volume and the highest amount of rehabilitation. 28 This study can be helpful to obese patients. 28 Spencer et al discovered the importance of combining prebiotics with diet.…”
Section: Prebiotics and Their Health Benefitsmentioning
confidence: 89%
See 1 more Smart Citation
“…57 59 Yet, the literature in cancer populations connecting exercise to changes in the microbiome warrants additional scrutiny. Sampsell et al 133 recently conducted a 12-week exercise intervention in 10 breast cancer survivors with reassessment after a 12-week washout period. No statistically significant pre-post differences in alpha or beta diversity were detected yet a follow-up mouse study yielded a trend toward lower tumour development in mice colonised with post-exercise microbiota versus those colonised with pre-exercise microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Mice colonized with post-exercise gut microbes exhibit significantly diminished tumor volume with enrichment of favorable cytokine profiles and reduced angiogenesis. Prebiotic fiber supplementation further compound the anti-tumor effects 112 . Although several clinical trials have advocated the beneficial and therapeutic effects of probiotic consumption in cancer patients 113 , merely a handful of clinical trials are focused on the impact of probiotics in breast cancer patients.…”
Section: Restoring the Gut Microbiota As An Effective Therapeutic Str...mentioning
confidence: 99%